Hubungan Asupan Energi, Protein dan Suplemen dengan Tingkat Kebugaran - -, Sugiarto (Media Ilmu Keolahragaan Indonesia, 2012)
The purpose of this study to analyze the relationship between the intake of energy, protein and supplements with the fitness level of participants Virenka Gym fitness in Bantul-Yogyakarta. Type of observational study design was cross-sectional study. Subjects were participants fitness male sex, taking supplements, doing fitness which totaled 50 people. Gym Virenka research sites in Bantul-Yogyakarta. Data collected include the intake of energy, protein, supplements, and fitness level. Data were analyzed using t-test and Mann Whitney test. The results: 1) The mean energy intake of the respondents were included in the fit category was 2274.1 ÃÂ± 303.1 kcal, and energy intake were included in the category of respondents did not fit 1567.7 ÃÂ± 165.4 kcal. 2) Respondents were included in the fit category of protein intake was 79.5 ÃÂ± 19.2 g and the less fit in the category of respondents was 58.5 ÃÂ± 12.8 g. 3) Intake of supplements to fit the group of 2.6 (1.3 to 6.8) and the less fit group 3.5 (1.2 to 5.6). Conclusion: There is significant correlation between energy intake with the fitness level of participants Virenka Gym fitness in Bantul, Yogyakarta, there was a significant association between the intake of protein to the fitness level of participants Virenka Gym fitness in Bantul, Yogyakarta, and there was no significant association between the intake of supplements with fitness levels Gym fitness Virenka participants in Bantul Yogyakarta.